2018
DOI: 10.23960/jpp.v8.i2.201806
|View full text |Cite
|
Sign up to set email alerts
|

Mental representations of 14-15 years old students about the light propagation time

Abstract: Mental representations of 14-15 years old students about the light propagation time. Objectives: The study of students' representations of physics concepts and phenomena constitutes a central part of science education research, as they play a decisive role in teaching. In the study presented here, we investigate the mental representations of 14-15 years old students about the light propagation time, before they were taught about it in school. Methods: The empirical data was gathered through an interview using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…To be sure, there is a difference between the two groups, one that is also statistically significant; however, the fact that a large number of children does not regard time as necessary for the propagation of light through space signifies the presence of a powerful intuitive thought pattern. This result is compatible with the findings of earlier research, which either collects qualitative data through simple conversations with the children (Guesne, 1984(Guesne, , 1985, or limits the samples to younger ages (Osborne, Black, Meadows, & Smith, 1993;Ravanis, 1991).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To be sure, there is a difference between the two groups, one that is also statistically significant; however, the fact that a large number of children does not regard time as necessary for the propagation of light through space signifies the presence of a powerful intuitive thought pattern. This result is compatible with the findings of earlier research, which either collects qualitative data through simple conversations with the children (Guesne, 1984(Guesne, , 1985, or limits the samples to younger ages (Osborne, Black, Meadows, & Smith, 1993;Ravanis, 1991).…”
Section: Discussionsupporting
confidence: 91%
“…Guesne (1984Guesne ( , 1985 found that the majority of 13-to 14-year-old children recognize light propagation time, albeit solely in the case of large distances. Another research has shown that 10-year-old children's perception of light propagation as instantaneous derives from the brevity of the distance between the light source and the receiver, or from the stronger power of the light source (Ravanis, 1991). Another current in research scholarship, albeit with a different direction than ours, is concerned with the understanding of relativistic time in the framework of Classical Physics and the Special Theory of Relativity (Otero, Arlego & Prodanoff, 2016;Otero & Arlego, 2018;Villani & Pacca, 1987).…”
Section: Theoretical Frameworkmentioning
confidence: 99%